Effect of Smart Software on Developing The Architectural Projects in Jordan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims at investigating impact of using smart software on developing the architectural projects in Jordan.To achieve objectives of the research, the researcher used the quantitative research method to extract percentages, standard deviation, and frequencies.The main instrument used for collecting the primary data was the questionnaire, while secondary data was collected by referring to the previous studies that have addressed the use of smart software in the architectural projects.Study population consisted of design engineers in the construction firms in Jordan, while research sample has been selected through the use of the simple random sampling technique which consisted of (150) design engineers.Responses of the engineers to the questionnaire’s clauses were analyzed using (SPSS) software.Based on the results, it is recommended:-              The necessity for learning from the experience of the developed countries in using the smart software to be able to improve and develop the work environment in the architectural projects.-              The need for executing architectural projects through the use of smart software to reach big projects relevant to the society.-              The need for conducting more studies about the smart software and linking them with other variables